Effect of Biosynthesised Nano-zinc on Blood Biochemical Profile, Antioxidant Status and Immune Response in Vanaraja Birds - Kumar, M. Ravi; Roy, Barun; Kannan, A.; Shanmugam, M.; Venkateswarlu, R.; Kannaki, R.; Kumar, M. Muthu; Rani, K. Sudha (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during December, 2021 to February, 2022 at the location of research was poultry farm, directorate of poultry research Hyderabad, Telangana, India to investigate the efficacy of biosynthesized nano-zinc as a substitute for traditional zinc salt in the diet of Vanaraja chickens, focusing on its impact on blood biochemical profile, antioxidant status, and immune response. A total of 324-day-old Vanaraja chicks were randomly assigned to six dietary treatments, including a negative control (no supplemental zinc), a basal diet supplemented with zinc oxide (60 mg Zn kg-1), and four groups receiving biosynthesized nano-zinc at levels of 15, 30, 45, and 60 mg Zn kg-1 diet. The trial spanned 56 days with 9 replicates per treatment group. Results demonstrated that nano-zinc supplementation at 30 mg kg-1 significantly (p<0.05) improved humoral immunity compared to the control, matching the immune response achieved with 60 mg kg-1 zinc oxide. No adverse effects on serum enzyme profiles or biochemical parameters were observed across treatments, indicating the safety of nano-zinc as a feed additive. From the current study, it may be concluded that the conventional zinc oxide can be replaced with nanoparticle forms at a reduced level without any adverse effect on health assessed through serum biochemical profile. In order to recommend the level of dose reduction, more studies with different breeds, indifferent agro-climatic zones during different seasons are recommended.